Interleukin-27 is a potential marker for the onset of post-transplant malignancies. Issue 1 (27th July 2018) - Pontrelli, Paola; Rascio, Federica; Zaza, Gianluigi; Accetturo, Matteo; Simone, Simona; Infante, Barbara; Furian, Lucrezia; Castellano, Giuseppe; Ditonno, Pasquale; Battaglia, Michele; Cormio, Luigi; Carrieri, Giuseppe; et al.
ABSTRACT: Background: Malignancies represent the third leading cause of post-transplant mortality worldwide. The main challenge for transplant physicians is a timely diagnosis of this condition. The aim of the study was to identify a soluble diagnostic marker for monitoring the development of post-transplant malignancies. Methods: This is a multicentre, observational, perspective, case–control study. We enrolled 47 patients with post-transplant solid neoplasia. As a control group we employed 106 transplant recipients without a history of neoplasia and matched them with cases for the main demographic and clinical features. We investigated the transcriptomic profiles of peripheral blood mononuclear cells from kidney graft recipients with and without post-transplant malignancies enrolled in two of the participating centres, randomly selected from the whole study population. Microarray results were confirmed by quantitative polymerase chain reaction (PCR) and enzyme-linked immunosorbent assay (ELISA) in the remaining patients from the same transplant centres and validated in a further independent group enrolled in two different transplant centres. Results: We identified 535 differentially expressed genes comparing patients with and without post-transplant malignancies (fold change ≥2.5; false discovery rate <5%). The cancer pathway was closely related to gene expression data, and one of the most down-regulated genes in this pathway was interleukin-27 (IL-27), a cytokine regulating anti-tumour immunity. Quantitative PCR and ELISA confirmed the microarray data. Interestingly, IL-27 plasma levels were able to discriminate patients with post-transplant neoplasia with a specificity of 80% and a sensitivity of 81%. This observation was confirmed in an independent set of patients from two different transplant centres. Conclusions: Our data suggest that IL-27 may represent a potential immunological marker for the timely identification of post-transplant neoplasia.